2020
DOI: 10.1111/jsr.13165
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac autonomic control during non‐REM and REM sleep stages in paediatric patients with Prader‐Willi syndrome

Abstract: Cardiac death is the second most prevalent cause in Prader-Willi syndrome (PWS).Paediatric patients with PWS often present cardiac autonomic dysfunction during wakefulness, obesity and sleep-disordered breathing. However, the extent of car-How to cite this article: Brito LC, Queiroga T, Franco RR, et al. Cardiac autonomic control during non-REM and REM sleep stages in paediatric patients with Prader-Willi syndrome. J

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
5
0
2
Order By: Relevance
“…Although exhibiting heterogeneity, PWS was the first microdeletion condition to be identified on chromosomal analysis with high resolution. In addition, it is a uniparental-disomic and gene-imprinting disorder epitomized by distinct phenotypic behavior [ 1 ]. The major signs consist of infantile hypotonia, intellectual disability, hypogonadism, and short stature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although exhibiting heterogeneity, PWS was the first microdeletion condition to be identified on chromosomal analysis with high resolution. In addition, it is a uniparental-disomic and gene-imprinting disorder epitomized by distinct phenotypic behavior [ 1 ]. The major signs consist of infantile hypotonia, intellectual disability, hypogonadism, and short stature.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, epidemiological records indicate the sporadic nature of the disease. Brito et al [ 1 ] record a prevalence rate of 1 in 16,000, while Butler et al [ 2 ] reported a prevalence of 1 in 24,590. Generally, prevalence estimates fall from 1 in 10,000 to 20,000 individuals in the United States, while global incidence rates range from 1 in 10,000 to 1 in 30,000 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of neurodevelopmental disorders, patients with attention-deficit/hyperactivity disorder (ADHD) show reduced vagally-mediated HRV after a task demand ( Robe et al, 2019 ). In addition, a relative cardiac autonomic imbalance (a lower parasympathetic modulation) has also been found in pediatric patients with Prader-Willi syndrome ( Brito et al, 2021 ). Concerning psychiatric disorders, patients with schizophrenia and bipolar disorder exhibit reductions in HRV, which have been linked to disease severity ( Benjamin et al, 2021 ).…”
Section: Heart Rate Variability Analysis As a Methods For Assessing C...mentioning
confidence: 99%
“…A disfunção do sistema parassimpático exacerbada pelos DRS foi relatada na literatura como outra possível disfunção em pacientes pediátricos com SPW. Foi constatado por Brito et al (2021) (57) que o desequilíbrio autonômico cardíaco devido à modulação cardíaca parassimpática prejudicada durante o sono de ondas lentas, resulta em aumento da frequência cardíaca mesmo sem a presença de qualquer doença cardiovascular e independente da obesidade. Estas diferenças cardiovasculares podem indicar um risco cardiovascular mais elevado mesmo durante a infância e, portanto, é prudente monitorar também a saúde cardiovascular dos pacientes pediátricos com SPW.…”
Section: Distúrbios Respiratórios Do Sono Na Spwunclassified